2005
DOI: 10.1159/000086844
|View full text |Cite
|
Sign up to set email alerts
|

Profilometric and Microradiographic Studies on the Effects of Toothpaste and Acidic Gel Abrasivity on Sound and Demineralized Bovine Dental Enamel

Abstract: The objective of this study was to assess the abrasive effects of toothpastes and acidic F gels on sound and demineralized enamel. Pairs of enamel specimens were cut from bovine incisors, embedded in epoxy resin and polished. An artificial subsurface lesion of 80–90 µm depth was created in one specimen from each pair. The samples were covered with adhesive tape, thereby exposing the enamel for abrasivity testing. All samples were divided into six groups of 15 and brushed with a slurry (1:3) of F gel or toothpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
57
1
8

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 33 publications
5
57
1
8
Order By: Relevance
“…This finding suggests that the pH may be an important factor when considering the impact of the toothpaste on the enamel surface. 13,15 G2 (Close-UP Whitening  ) presented a pH closest to 7 and altered the enamel surface when brushing was preceded by application of the bleaching agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests that the pH may be an important factor when considering the impact of the toothpaste on the enamel surface. 13,15 G2 (Close-UP Whitening  ) presented a pH closest to 7 and altered the enamel surface when brushing was preceded by application of the bleaching agent.…”
Section: Discussionmentioning
confidence: 99%
“…The concomitant use of abrasive toothpastes during at-home bleaching procedures reportedly increases the roughness of dental enamel. 11,[15][16][17][18] The purpose of this study was to evaluate the physical-chemical characteristics of the whitening toothpastes by determining their effect on bovine enamel surfaces during brushing after treatment by a bleaching agent. The classical alternative hypothesis that was investigated was: the composition of the tested toothpastes does not interfere with enamel surface roughness after the bleaching treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In this group, abrasion reached a plateau after 250 strokes and no further increase could be observed by application of 100 additional strokes. As shown by Kielbassa et al [2005], brushing with distilled water is nearly unable to remove sound enamel, while brushing with toothpaste slurry may remove sound enamel but to a lesser extent than demineralized enamel. Therefore, differences in enamel loss by toothbrushing with distilled water or toothpaste slurry might be related to the abrasivity of the toothpaste.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that the movement of agents associated with the toothbrushing abrasive in a dentifrice and the toothbrush bristles, can cause damage to the brushed substrate, capable of altering the restorative material roughness [11][12][13][14][15][16] . The abrasives in dentifrices have been related to dental wear (abrasion) and over time, can also cause an increase in the surface roughness of restorative materials, leading to greater plaque retention and composite pigmentation 12,13,15 . Mouthrinses have also been used for centuries for the purpose of providing oral health and cosmetic benefits 17 and in the last few years their use has attracted the curiosity of the researchers because of their ability to modify the surface of composite resins.…”
Section: Introductionmentioning
confidence: 99%